Por que medicina? Por que UFSCar?: uma análise crítico-reflexiva da graduação em medicina da Universidade Federal de São Carlos - Assumpção, Kin Shimabukuro Castro de (Universidade Federal de São Carlos, 2020)
This Undergraduate Thesis will follow the guidelines from UFSCar’s medical course’s Projeto Político Pedagógico (Political Pedagogical Project). The development of this thesis is a critical and reflexive narrative from the perspective of a student and his trajectory through out the six years of graduation. As such, it will follow a cronological line presenting all three cycles lived in the medical training with the duration of two years each. The first cycle, also known as basic cycle has the purpose of introducing all basic fields needed to become a medical doctor. Following an active learning methodology called “Espiral Construtivista” it’s also a moment for the student to learn how to become more independent and to find ways to study finding adequate and up-to-date study sources for what you’re looking for. The second cycle follows the basic cycle with amelioration of clinical and ambulatorial practice and beggining to enphasize some pathologies and branching the medical knowledge into greater fields The third and final cycle is also known as “Internato” being a real immersion of the student in what is expected as a graduated medical doctor. The end of graduation was profoundly marked by COVID-19’s pandemic and because of it, this weird moment in anyone’s life deserves special atention, even more when we talk about someone who’ll work in healthcare. Finally, the conclusion is that even with insecurities and anxieties, the thought of every moment lived up to this point shows us that the progress made is undeniable and the perspective of betterment is always possible
Why medicine? Why UFSCar?: a critical-reflexive analysis of undergraduate medicine at the Federal University of São Carlos
Keywords: Metodologia ativa; Medicina; Espiral Construtivista; Narrativa Crítico Reflexiva; CIENCIAS DA SAUDE::MEDICINA